Characterization of two iron bullets from the royal ammunition factory of Eugi (Spain) - Zalakain I.; Berlanga C.; Alvarez L.; Asa L.; Labé P.; Rivero P.; Valencia J.; Rodríguez R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, a comparative analysis of two iron bullets found in The Royal Ammunition Factory of Eugi in Navarra (Spain) was performed. Both bullets presented a spherical shape with a relatively good state of preservation, belonging to the last years of the factory production (1766-1850). Several techniques such as microhardness, X-ray fluorescence (XRF), light (LM) and scanning electron microscopy (SEM), optical mission spectroscopy (OES) and energy dispersive X-ray spectroscopy (EDX) analysis were used in order to identify the manufacturing process of the two bullets. The analyses of the microstructures carried out by LM and SEM showed that one bullet was composed of white cast iron with a pearlitic matrix, steadite and graphite; while the other was composed of grey cast iron with a pearlitic matrix, graphite and a low amount of steadite. The chemical analysis of the bullets carried out by OES indicated significant differences in the amount of silicon and phosphorous. The variation in silicon content could suggest that the foundry temperature under oxidizing environment varied during the casting. The SEM and EDX analyses showed both bullets had manganese sulphide inclusions but only one of the bullets exhibited titanium and vanadium inclusions. The microhardness analyses carried out revealed Vickers hardness differences along the diameter. This variation could be explained by the differences in cooling rate along the diameter. Based on the physical characteristics of the bullets and on the obtained results, it can be concluded that one of the bullets could have been used as a grapeshot projectile and the other one as a bullet for ribauldequins. In addition, calcined ore and slag found in this factory were also analysed. The variation found in their chemical composition corroborated that the foundry temperature employed during the manufacturing process was low, the slag being enriched in Si, Al and Mn elements.